Effectiveness of the Ibis Paint X-Based E-Module in Technical Drawing for Fashion Technology Training - Cahyani, Yustin Sagita Dwi; Sutopo, Yeri; Kusumastuti, Adhi (Universitas Negeri Semarang, 2024)
This study aims to test the effectiveness of an e-module based on the Ibis Paint X application in improving learning outcomes of participants in the Technical Drawing material of the Fashion Technology vocational program. The research method uses a quantitative approach with a one-group pretest-posttest design. The instruments used include pre-tests and post-tests, as well as user response questionnaires. Data were analyzed using normality, homogeneity, and N-Gain tests. The results show that the use of the e-module significantly improves the understanding of training participants, with high effectiveness based on the N-Gain test results. Additionally, user responses indicate that the e-module is practical and suitable for use in training. These findings suggest that the integration of the Ibis Paint X application in the e-module supports adaptive and effective digital learning in vocational training environments.